Bioinspired ionic liquid-graphene based smart membranes with electrical tunable channels for gas separation. (June 2022) - Widakdo, Januar; Huang, Tzu-Jung; Subrahmanya, T.M.; Austria, Hannah Faye M.; Chou, Hung-Lung; Hung, Wei-Song; Wang, Chih-Feng; Hu, Chien-Chieh; Lee, Kueir-Rarn; Lai, Juin-Yih
Highlights: β-PVDF increases up to 79.84%, making the membrane have good conductivity and sensitive to the electric stimuli. With a high IL concentration of [BMIM][BF4] and 3 V electricity, the molecular sieving performance increased from 81.91 to 193.55 Barrer of CO2 permeability and 58.4 to 129.03 of CO2 /N2 selectivity, exceeding the 2008 Robeson upper bound. PALS data shows that the curve became narrow, and the interface increased; this indicates that gas molecules can easily pass through the system. DFT simulation of the single CO2 molecule on the PG-BF4 10 wt.% and PG-PF6 10 wt.% membrane reported the adsorption energy of carbon dioxide −3.1 eV and −3.0 eV. The O2 adsorption energies is +0.07 eV and +0.8 eV. A negative value in the adsorption energy means that CO2 shows more attraction to adsorb and diffuse in the system. Abstract: Fast response and adjustable selectivity have always been the main goals pursued by the manufacture of smart membranes. Herein, we demonstrate smart membrane materials composed of ionic liquid (IL), PVDF, and graphene. The infusion of IL aims to increase the β crystal phase of PVDF, which is also assisted by the presence of graphene in the system. β-PVDF increased from 48.9% to 79.8% when the ionic liquid content [BMIM][BF4] increases from 2 to 10 wt.%, which makes the membrane more electro responsive. The optimum membrane of PG-BF4 10 wt.%, upon supply of 3 V DC electricity, exhibited CO2 /N2 selectivity value of about 129.03 and CO2 permeability of 193.55 Barrer, exceeding the 2008 Robeson upper bound. Positron Annihilation Lifetime Spectroscopy (PALS) data and Density Function Theory (DFT) simulations helped to realize the mechanism of selective transportation of CO2 gas through the membrane both theoretically and experimentally. PALS results indicated that the free volume of PVDF increased; indicating that CO2 molecules can easily pass through the system. DFT simulation revealed that the CO2 molecules show more attraction and lower adsorption energy under electric stimuli, confirming that CO2 molecules adsorb and diffuse quickly through the system than O2 or N2 . Overall, tuning the free volume and molecular interactions within the membrane channels provide a rational molecular sieving approach to improve membrane selectivity.